ChemInform Abstract: A Highly Enantioselective Hydrogenation of Silyl Enol Ethers Catalyzed by Chiral Frustrated Lewis Pairs. Issue 12 (March 2015) - Wei, Simin; Du, Haifeng
Abstract Highly enantioselective metal‐free hydrogenation of silyl enol ethers is achieved by combining P(tBu)3 with a chiral borane generated in situ by hydroboration of an axial‐chiral diene with HB(C6F5)2 as a frustrated Lewis pair catalyst.